2004
DOI: 10.1021/jo0483623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Function of Gene lndM2 Encoding a Bifunctional Oxygenase-Reductase Involved in the Biosynthesis of the Antitumor Antibiotic Landomycin E by Streptomyces globisporus 1912 Supports the Originally Assigned Structure for Landomycinone

Abstract: The angucycline antibiotic family of the landomycins displays potent antitumor activity. To elucidate early post polyketide synthase (PKS) tailoring steps of the landomycin E biosynthetic pathway in Streptomyces globisporus 1912, the mutant S. globisporus M12 was prepared through gene replacement experiment of lndM2. It encodes an enzyme with putative oxygenase and reductase domains, according to sequencing of the gene and its counterpart lanM2 from S. cyanogenus S136 landomycin A biosynthetic gene cluster. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
57
0
6

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 25 publications
4
57
0
6
Order By: Relevance
“…[5] In particular, it was recently shown that the non-glycosylated angucyclinones tetrangomycin (11) and rabelomycin (12) can be further converted into landomycin E (1) by the lndF mutant F133, and thus 11 and 12 are biosynthetic intermediates. [12] The results described here confirm this description of a-compared to the urdamycin pathway-later first glycosylation step. The fact that none of the new prejadomycin C-glycosides including monoglycoside 7 could be further modified by the oxygenases that exist in S. globisporus ΔlndE (urdGT2), for example, by LndM2 and LndZ4/Z5, shows that these oxygenases require non-glycosylated substrates.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…[5] In particular, it was recently shown that the non-glycosylated angucyclinones tetrangomycin (11) and rabelomycin (12) can be further converted into landomycin E (1) by the lndF mutant F133, and thus 11 and 12 are biosynthetic intermediates. [12] The results described here confirm this description of a-compared to the urdamycin pathway-later first glycosylation step. The fact that none of the new prejadomycin C-glycosides including monoglycoside 7 could be further modified by the oxygenases that exist in S. globisporus ΔlndE (urdGT2), for example, by LndM2 and LndZ4/Z5, shows that these oxygenases require non-glycosylated substrates.…”
supporting
confidence: 85%
“…Major structural differences were found in the assembly of the sugar moieties and in the oxygenation pattern of the polyketide core moiety. [1,4,5,[10][11][12] The availability of the biosynthetic gene clusters of urdamycins and landomycins [7,[13][14][15][16][17] made it possible to track down the genes encoding the biosynthetic enzymes responsible for the unique structural features of the two types of compounds, which are also responsible for the significant variations in the biological activities of these related anti-cancer drugs. [18] The overall structural and biosynthetic similarity between these two closely related sets of antibiotics allowed several successful combinatorial, biosynthetic gene-combination experiments, leading to new hybrid molecules.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For the instruments/NMR methods used, see Ref. [42]. The labeled sodium [1,2-13 C 2 ]acetate used in the incorporation experiment was obtained from Isotec (Miamisburg, OH, USA).…”
Section: Methodsmentioning
confidence: 99%